The devil in disguise a comparative study of Thomas Mann's "Doktor Faustus" (1947) and Klaus Mann's "Mephisto" (1936), focussing on the role of art as an allegory of the rise and fall of Nazi Germany - French, Rebecca S C (Rhodes University, Faculty of Humanities, School of Languages, 2008)
This thesis compares the novels Doktor Faustus: das Leben des deutschen Tonsetzers Adrian Leverkühn, erzÃ¤hlt von einem Freunde (Thomas Mann) and Mephisto: Roman einer Karriere (Klaus Mann), insofar as they are portrayals of the situation in Germany during the Third Reich. Essentially a comparative study, I explore similarities and differences "“ thematic and conceptual "“ by situating both novels in their socio-historical moment (Chapter 1), exploring their conceptions of German national identity (Chapter 2), tracing intertextual connections to other works (Chapter 3), and, finally, examining their understanding of and reliance on art as insofar as it provides the allegorical framework for their respective portrayals of Nazi Germany (Chapter 4).
Keywords: Mann, Thomas, 1875-1955 --bDoktor Faustus; Mann, Klaus, 1906-1949 -- Mephisto; Arts, German -- 20th Century; Art, Germany -- 20th Century; National socialism in art; National socialism in literature